Statistical process control for monitoring a diffusion process - Tsai, Tzong-Ru; Chang, Shing I; Chou, Shih-Hsiung; Chiang, Jyun-You; Sung, Wen-Yun (My University, 2012)
This study presents a new statistical process control (SPC) procedure for a process together with degradation and diffusion effects. One of such examples is the initial cool-down process of high-pressure hose production. The air temperature readings during the initial cool-down process often exhibit a non-increasing trend with a diffusion effect in that profiles generated from cycle to cycle deviate from each other more over time. A new charting procedure using the Wiener diffusion model is developed in this article. A real data set, generated from the cool-down process of high-pressure hose production, is used to demonstrate the application of proposed method.
Keywords: Control chart; Normal distribution; Profile monitoring; Statistical process control; Wiener diffusion model